Cytogenetics and crop improvement - Bai, K.V.; Hahn, S.K. (1992)
In many crop species, the transfer of agronomically important genes from wild species has been possible through chromosomal manipulations. Haploids have been useful in the production of homozygous lines. Induced polyploids find direct use in crops in which the seed is not the economic produce. As illustrated by triticale and wheat, the development of amphiploids and addition and substitution lines are important in crop improvement. Meiotic modifications resulting in 2n gametes appear to be useful potential tools for unilateraly/bilateral sexual polyploidization. Coupled with recent advances in several areas, including chromosome banding techniques and isozyme analysis, cytogenetics can play a significant role in crop improvement.